1991
DOI: 10.4049/jimmunol.147.11.4014
|View full text |Cite
|
Sign up to set email alerts
|

VDJ genes in VHa2 allotype-suppressed rabbits. Limited germline VH gene usage and accumulation of somatic mutations in D regions.

Abstract: In this study we investigate the molecular genetic basis for VHa- Ig. Knowing that the expression of VHa allotype Ig is suppressed by neonatal injection of rabbits with anti-VHa allotype antibody, and that the decreased level of VHa allotype Ig, VHa+, in the suppressed rabbits is compensated for by an increase in VHa- Ig, we determined the nucleotide sequences of 41 VDJ genes from a2/a2 rabbits neonatally suppressed for the expression of a2 Ig. We compared these nucleotide sequences to each other and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This increase presumably reflects ongoing IgH gene diversification as well as increased proliferation. Rabbits diversify their IgH genes by both somatic gene conversion as well as somatic hyperpointmutation (22)(23)(24). Winstead and Knight (unpublished data) recently showed that both of these processes contribute to IgH gene diversification in PLN of immunized rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This increase presumably reflects ongoing IgH gene diversification as well as increased proliferation. Rabbits diversify their IgH genes by both somatic gene conversion as well as somatic hyperpointmutation (22)(23)(24). Winstead and Knight (unpublished data) recently showed that both of these processes contribute to IgH gene diversification in PLN of immunized rabbits.…”
Section: Discussionmentioning
confidence: 99%